13 Transforming Archaeology, Transforming Materiality. Issue 1 (September 2015) - Joyce, Rosemary A.; Overholtzer, Lisa; Robin, Cynthia
ABSTRACT The archaeological contribution to materiality has to date been less widely appreciated by practitioners outside the subdiscipline. This chapter argues that this is in part due to the identification of archaeological materiality with things, objects, or material culture, deriving from the twentieth‐century history of Americanist archaeology in particular. While archaeologists have made important contributions to debates about the agency of objects, object biographies, and critiques of object/subject dichotomies, there are specific perspectives that archaeology could contribute that derive from the nature of archaeological sites as places consisting of material traces. This article examines in depth the concept of trace as it is used in broader social theory, and as it is instantiated in archaeological materialities. It is argued that for materialities of everyday life, in particular, traces have been the most effective kinds of materialities explored by archaeologists.